Recursos didácticos tecnológicos y su incidencia en el proceso de enseñanza aprendizaje en los niños y niñas de primer año de educación básica de las escuelas fiscales mixta Manuel Isaac Encalada Zúñica y Aurelio Prieto Muelas, de la parroquia Buenavista, cantón Pasaje, período 2012-2013. - Palma Palma, María Domitila (2013)
This research paper presents very briefly about the technological teaching resources and its impact on the teaching-learning process, since most teachers are not adequately prepared for mastering educational software, generating demotivation students in classes and little desire to learn the content.